1975
DOI: 10.1159/000114677
|View full text |Cite
|
Sign up to set email alerts
|

Occult Disorders of the Cerebrospinal Fluid Dynamics

Abstract: Workable criteria are proposed that allow early recognition of mild forms of occult hydrocephalus and correlated disorders. Two groups of patients are analyzed, i.e. a group of twelve mild but classical forms of low-pressure hydrocephalus and another group of 20 patients with atypical clinical forms of disorders of the CSF dynamics. Two control groups are presented for neuropsychological comparison purposes: a normal control group of 50 subjects and a small group of three commissurotomized subjects. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Botez et al [7] found 10 patients with loss of consciousness and falls and attacks of gen eral limpness in 32 patients with pure NPH or NPH with cortical atrophy. They stressed the clinical importance of these attacks in the diagnosis and management of NPH pa tients [10] and wondered why these falls are so seldom described in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Botez et al [7] found 10 patients with loss of consciousness and falls and attacks of gen eral limpness in 32 patients with pure NPH or NPH with cortical atrophy. They stressed the clinical importance of these attacks in the diagnosis and management of NPH pa tients [10] and wondered why these falls are so seldom described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this and in spite of the use of advanced methods of investiga tion, the outcome of surgery is still unpre dictable [2], It is generally accepted that the clinical picture and not the result of radiological investigations is the most important crite rion for the diagnosis NPH [2], It is also accepted that the presence of the complete clinical 'triad', namely gait disorder, demen tia and urine incontinence, is the most reli able sign for predicting the outcome of sur gery [3]. The gait disturbance, however, may appear without or may precede the other symptoms [4], Many additional clinical characteristics have been mentioned: fluc tuating and progressive course [5], improve ment after lumbar puncture [5,6], tonic foot reflex or grasp reflex of the foot [7], parkin sonian signs [8] and behavioural distur bances [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9) The Kohs Block Design Test is recognized as a standard clinical tool for detection of visuospatial disorganization, which indicates malfunction of the parietal lobe. 6,26) We used this test in its complete form with 17 designs and calculated the intelligence quotient (IQ) according to the Manual for Kohs Block Design Test (catalogue No. 37000; Stoelting, Chicago, Ill., U.S.A.).…”
Section: Methodsmentioning
confidence: 99%
“…(3) There is only one reported case of latent polyneuropathy responsive to folic acid therapy [14], in which the authors found an abnormal jejunal biopsy as well as low serum, red cell and CSF folate concentrations without any evidence of anemia. (4) Since 1974 [8], we have been using a neuropsychological battery to detect occult hydro cephalus and cerebral atrophies; the neuropsychological assessment is fol lowed by radionuclide cistemograms with m In and computerized transaxial tomography (CTT) of the brain. We have started this comprehen sive method of examination in all metabolic and nutritional disorders in cluding vitamin B," [9] and folic acid deficiencies.…”
Section: Introductionmentioning
confidence: 99%